Diurnal Variations of Size‐Resolved Bioaerosols During Autumn and Winter Over a Semi‐Arid Megacity in Northwest China. (20th May 2021) - Yang, Liu; Shen, Zhenxing; Wang, Diwei; Wei, Junqiang; Wang, Xin; Sun, Jian; Xu, Hongmei; Cao, Junji
Abstract: Bioaerosols have a major negative effect on air quality and on public health by causing the spread of diseases. This study evaluated the bioaerosol composition and variation in a semi‐arid megacity of northwest China from October 2019 to January 2020 using an Andersen six‐stage impactor sampler. The size distribution, diurnal variations of the concentrations of airborne bacteria, airborne fungi, and total airborne microbes (TAM) were investigated in autumn and winter. The mean concentrations of airborne bacteria, fungi, and TAM were 523.5 ± 301.1 colony‐forming units (CFU)/m 3, 1318.9 ± 447.8 CFU/m 3, and (7.25 ± 1.90) × 10 6 cells/m 3, respectively, in autumn and 581 ± 305.4 CFU/m 3, 1234.4 ± 519.9 CFU/m 3, and (5.96 ± 1.65) × 10 6 cells/m 3, respectively, in winter. The mean bioaerosol concentrations were slightly higher on nonhaze days than on haze days, but the difference was not statistically significant. Higher ambient particulate matter levels and atmospheric oxidation capacity inhibited bacteria survival. The diurnal maximum bioaerosol concentration was observed in the morning in autumn, whereas in winter, bioaerosols did not exhibit such a distribution, the impact of human activities on bioaerosols was still uncertain. The size of airborne bacteria exhibited a bimodal distribution, whereas a unimodal pattern was observed for fungi and TAM. Most bacteria, fungi, and TAM were distributed in the respirable ranges from trachea and primary bronchi to alveoli, indicating that bioaerosols have a high risk of being inhaled and causing respiratory diseases in Xi'an. Key Points: The diurnal pattern of bioaerosol in autumn was clearly different with that in winter Airborne bacteria exhibited bimodal distribution while unimodal pattern was observed for fungi and total airborne microbes High particulate matter levels and atmospheric oxidation capacity inhibited bacteria survival in winter